A promising method to improve the bias-stress and biased-radiation-stress stabilities of solution-processed AlOx thin films. (March 2022) - Fang, Yuxiao; Xu, Wangying; Zhao, Tianshi; Mitrovic, Ivona Z.; Yang, Li; Zhao, Chun; Zhao, Cezhou
Abstract: The effects of hydrogen peroxide (H2 O2 ) on the device properties and stabilities of solution-processed AlOx metal-oxide-semiconductor capacitors (MOSCAPs) were investigated. It is demonstrated that H2 O2 is a strong oxidizer to decompose precursor residuals, reduce oxygen vacancy (Vo ) and defects density of solution-processed AlOx thin films. The interface quality and the bias-stress (BS) stability of AlOx MOSCAPs were improved by employing H2 O2 . Furthermore, through carrying out on-site measurements, 7.5 M H2 O2 AlOx MOSCAPs exhibited ignorable radiation-induced oxide traps and interface traps under biased-radiation-stress (BRS) with a total dose up to 42 Gy (SiO2 ). The 7.5 M H2 O2 AlOx MOSCAPs also demonstrate the ability to recover under radiation after the bias was interrupted. The reduced number of Vo and high AlOx concentration of 7.5 M H2 O2 AlOx could suppress the radiation-induced trapping/de-trapping behavior among the AlOx bulk and the breaking of Si–H bonds at the AlOx /Si interface. Besides, through biased-illumination-stress (BIS) measurements, the breaking of Si–H bonds under negative biased-radiation-stress (NBRS) was further proved. The results demonstrate that employing H2 O2 in the solution-process is simple and effective; it has significant potential to improve the stabilities of large-area electronics for nuclear and aerospace applications. Highlights: H2 O2 was employed to improve the radiation hardness of solution-processed AlOx . On-site measurements under irradiation were carried out. 7.5 M H2 O2 AlOx had ignorable radiation-induced oxide and interface traps. 7.5 M H2 O2 could suppress radiation-induced trapping/de-trapping behaviors. The breaking of Si–H bonds under NBRS was proved by BIS measurements.